Stabilizing Gap of Pole Electric Arc Furnace Using Smart Hydraulic System - Sallom, Maher Yahya; Khaleel, Riyam Neamah (Al-Khwarizmi Engineering Journal, 2015)
Abstract Electric arc furnace applications in industry are related to position system of its pole, up and down of pole. The pole should be set the certain gap. These setting are needed to calibrate. It is done manually. In this research will proposed smart hydraulic to make this pole works as intelligent using proportional directional control valve. The output of this research will develop and improve the working of the electric arc furnace. This research requires study and design of the system to achieve the purpose and representation using Automation Studio software (AS), in addition to mathematically analyzed and where they were building a laboratory device similar to the design and conduct experiments to study the system in practice and compared with simulation. Experimental tests show that the performance of electro hydraulic closed loop system (EHCLS) for position control is good and the output results are good and acceptable. The practical results and simulation using (AS) software are clearly convergence. It was concluded that the possibility of the implementation of this project in industrial processes such as electric arc furnaces to control the distance between the pole and smelting molten material in addition to other applications. Keywords: Proportional valve, LVDT, Electro hydraulic, electric furnace, Automation studio.